Processos educativos em práticas docentes de sociologia : perspectivas para a educação das relações étnico-raciais no ensino médio - Souza, Erivelto Santiago (2017)
This study aims to identify, describe and understand The development of education of ethnicracial relationships in a teaching practice held in Sociology classes in high school that help in the appreciation of history and culture of Afro-Brazilians and Africans. It is anchored in studies on educational processes unleashed by social practices, education of ethnic-racial relationships and sociology teaching. The research participants are students and the Sociology teacher of a second year high school class of a state public school in the municipality of São Carlos/SP. With the objective of identifying educational processes unleashed in teaching practice in Sociology classes, We opted for a theoretical-methodological stance based on phenomenology. Thus, to collect and analyze the data, conversations, participant observation, coexistence, interviews and conversational wheels with participants of the research. The data collected were organized in the following categories of analysis: relations, educational processes - teaching strategies, educational processes - to think sociologically, valuation of ethnic-racial belonging, reflection on practice and intervention - research as a social practice. The analysis of the data provides us with indications and references that Sociology teaching makes it possible to rethink ethnic-racial, social, pedagogical relations that aim to ensure student appreciation and strengthen their strengthen ethnic-racial belonging. Possibilities of developing the education of ethnic-racial relationships in the teaching of Sociology. Research has contributed to the strengthening of education of ethnic-racial relationships as students become more attentive, curious and critical about ethnic-racial inequalities and have developed skills to overcome distorted visions. The research also allowed to generate subsidies for the teaching of Sociology in basic education in the sense of developing classes based on the epistemological principles: “estrangement” e “Denaturalization”.